Evolving Security Landscape of Nepal-China Relations - Kunwar, Nawaraj Bikram (Journal of APF Command and Staff College, 2023)
Nepal-China relations have been cordial for centuries. The relationship is based on the principles of panchasheel, mutual trust and respect. China's overall policy and interests in Nepal revolve around stability, security, economic development and geopolitics. The changes in regime, either the Shah Monarchy or the Federal Democratic Republic Government, have never been the issue in the unremitting mutual relations between the two countries. However, in the republic era, the security landscape of the Nepal-China relationship has been evolved due to Nepal's geostrategic location and its vulnerability, China's growing military and economic power, the US's China containment strategy and use of soft power; and India's concerns about Chinese growing engagement in Nepal have raise various questions and security implications for Nepal- China relations. The researcher has used the qualitative approach to analyze the Nepal-China relation and security dynamics after 2007. It mainly used diplomatic, military and economic aspects of DIME instruments of national power as a framework of analysis. Nepal must comprehend the sensitivity of China and India, along with other regional and international powers, regarding their security concerns and implement prudent policies prioritizing national interests. Given the evolving dynamics of global power relations and advancements in regional and international arenas, Nepal's nonalignment policy must become more productive, ensuring constructive engagement with China, India and extra-regional powers.